The continuous strength method for the design of cold-formed steel non-slender tubular cross-sections. (15th November 2018) - Yun, Xiang; Gardner, Leroy
Highlights: FE models validated against test results on cold-formed steel SHS/RHS. Validated FE models used to perform parametric studies considering key parameters. EN 1993-1-1 and AISC-360-16 provisions assessed using test and FE data. CSM extended and modified to cover the design of cold-formed steel SHS/RHS. Reliability of different methods evaluated by means of statistical analyses. Abstract: Cold-formed steels typically exhibit a rounded stress-strain response with gradual yielding merging into strain hardening. This form of stress-strain curve is at odds with the elastic, perfectly plastic material model that underpins many of the provisions set out in current structural steel design standards. In particular, the beneficial influence of strain hardening on cross-section capacity is neglected. The continuous strength method (CSM) is a deformation-based design method that enables material strain hardening properties to be exploited, thus resulting in more accurate and consistent capacity predictions. The aim of this study is to extend the CSM to the design of cold-formed steel non-slender tubular cross-sections subjected to compression, bending and combined loading, and to verify the proposals through comparisons with existing test data from the literature and finite element results generated herein. The finite element models were first developed and validated against test results on cold-formed steel cross-sections collected from the literature. An extensive parametric study was then conducted to generate additional data over a wider range of cross-section geometries, slendernesses and loading conditions. The numerical results together with the experimental results were then compared with capacity predictions, calculated according to the current design rules in European Standard EN 1993-1-1 (2005) and American Specification AISC-360-16 (2016) as well as the CSM. The CSM is shown to provide more accurate and consistent design predictions for cold-formed steel cross-sections under different loading conditions than those obtained from existing design methods. The improvements arise from the use of the continuous deformation based design approach, as well the rational exploitation of strain hardening. Finally, the reliability levels of the different design methods were assessed by conducting reliability analyses in accordance with EN 1990 (2002).